CONTRIBUTION OF ILLITIZATION OF SMECTITE TO OVERPRESSURE GENERATION ON THE ONSHORE OF THE EAST JAVA BASIN - TRIZANI ( NIM: 22015029), ELFARINO
The East Java Basin is an overpressured basin. Previously, overpressure in this basin was thought to be caused by loading mechanism. This loading mechanism is characterized by constant effective stress in overpressure zone. However, this study reveals that the average effective stress in overpressure zone in the study area decreases of about 5.47 MPa/km. This circumstance indicates the presence of non-loading mechanism. The non-loading mechanism could be caused by illitization of smectite. The illitization causes the mineral size to decrease into smaller grain and results in water thus decreasing the effective stress. The result of clay mineral analysis by using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Energy Dispersive X-Ray (EDX) shows that the amount of smectite is Ã‚Â± 25% of total clay mineral and it is transformed into illite at the temperature of 85˚C. This illitization of smectite gives some contribution into overpressure magnitude and decreasing the effective stress. Morevoer, this transformation causes the difference in clay mineral composition affecting normal compaction trend in the study area. This normal compaction trend is used to improve pore pressure estimation in the study area, and it results in better overpressure estimation. This study also results in smectitic and illitic compaction lines specific for the East Java Basin. The mechanism generating overpressure in the study area is loading and non-loading mechanisms (illitization of smectite). The contribution of the illitization to overpressure magnitude is proportional to the amount of smectite.